Psikologi pendidikan perkembangan anak usia dini - Oktami, Khaisya Nabila (Maliki Interdisciplinary Journal, 2024)
Early childhood educational psychology is the field that studies how people learn and develop psychologically, especially during the critical development of early childhood. Children experience rapid cognitive, social, emotional and motor development during this period. Based on the principles of psychology, early childhood education can provide a strong foundation for optimal development for children. The psychology of early childhood education studies and understands various child behaviours, both overt and covert, in order to provide appropriate and planned stimulation and intervention. By understanding child development psychology, teachers and parents can better influence children’s development by paying attention to children’s behaviour and mentality.